2017
DOI: 10.1007/s10433-017-0447-y
|View full text |Cite
|
Sign up to set email alerts
|

Exploring predictors of life satisfaction and happiness among Siberian older adults living in Tomsk Region

Abstract: Despite the growing interest in studying factors affecting subjective well-being of older adults, little research has been conducted on vast territory of Siberia (Russia) with large population. To address this lack of evidence, we explored the relationship between subjective well-being and social aspects (social and emotional support, social network, and social activities), living conditions (standards of living and residence area), self-reported health, and demographic characteristics in older adults living i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 58 publications
(118 reference statements)
3
7
0
Order By: Relevance
“…This phenomenon may also explain the reason why their social functioning and vitality domain improved and also echo the findings that participating in physical activities, leisure, social interaction, and helping others may fulfill positive emotions. [56][57][58][59] In line with previous studies, 35,36,40 the current study found that there were no significant improvements in the domains of bodily pain and role limitations due to emotional problems. This might be attributed that the PALM program was not designed for decreasing pain, instead emphasizing adapting or modifying the way of executing meaningful occupational activities to maintain the level of physical activity.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This phenomenon may also explain the reason why their social functioning and vitality domain improved and also echo the findings that participating in physical activities, leisure, social interaction, and helping others may fulfill positive emotions. [56][57][58][59] In line with previous studies, 35,36,40 the current study found that there were no significant improvements in the domains of bodily pain and role limitations due to emotional problems. This might be attributed that the PALM program was not designed for decreasing pain, instead emphasizing adapting or modifying the way of executing meaningful occupational activities to maintain the level of physical activity.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, the participants mentioned that they engaged in outdoor activities together and utilized the resources introduced in the program. This phenomenon may also explain the reason why their social functioning and vitality domain improved and also echo the findings that participating in physical activities, leisure, social interaction, and helping others may fulfill positive emotions 56–59…”
Section: Discussionmentioning
confidence: 53%
“…Self-rated health is a strong predictor of subjective well-being for older adults 1 , and it was significantly associated with flourishing in rural and urban areas. Similar findings have been reported in Malaysia 33 , Thailand 40 , and Russia 42 . Satisfaction with health falls rapidly with age in the populations of post-Soviet countries, including Mongolia, in part because of poor quality health care 43 .…”
Section: Discussionsupporting
confidence: 89%
“…At the same time, as in previous studies, personal and family-related factors were unrelated to flourishing in our urban subsample. Family relationships were essential to older adults’ well-being in Thailand 40 , networks with intimate people were necessary to older adults’ survival in Siberia 42 , the absence of children’s support created problems for older Koreans 57 , and a number of children were a strong predictor of well-being for older adults in Japan 50 . In Mongolia, family relationships are central, and the aforementioned rural-to-urban migration of younger generations highlights the adverse effects on older adults in rural areas 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Literature concerning life satisfaction predictors have addressed social aspects (e.g. social relationships and social support) 18,[23][24][25][26][27][28][29] , personality traits and physical activity 16 , leisure physical activities 13 , self-rated measurements of health 23,24,27,30,31 and psychological well-being 32 .…”
Section: Introductionmentioning
confidence: 99%